Effect of montmorillonite (MMT) content on the mechanical, oxygen barrier, and thermal properties of rice husk/MMT hybrid filler-filled low-density polyethylene nanocomposite blown films. (July 2016) - Majeed, Khaliq; Hassan, Azman; Bakar, Aznizam Abu; Jawaid, Mohammad
Montmorillonite (MMT)/rice husk (RH) hybrid filler-filled low-density polyethylene (LDPE) nanocomposite films, containing 0, 2, 3, 4, 5, and 6 wt% MMT (based on the total weight) were prepared by extrusion blown film. The films were characterized by morphological, mechanical, oxygen (O2 ) barrier, and thermal properties. The delamination of MMT layers evidenced from X-ray diffraction results suggests an increase in the interlayer distance and shows intercalated structure of the nanocomposites. Adding MMT did not adversely affect the interfacial morphology, as confirmed by scanning electron microscopy. Addition of MMT into the LDPE/RH system improved the mechanical and O2 barrier properties. For instance, tensile strength, tensile modulus, and tear strength increased by 8, 10, and 5%, respectively, with the addition of 3 wt% MMT. Further, the O2 barrier of the composite films improved more than twofold by adding 4 wt% MMT. Initial degradation temperature of LDPE/RH composites increased with the incorporation of MMT suggesting that the nanocomposites are more thermally stable than LDPE/RH composites.